Towards safer helmets: characterisation, modelling and monitoring - Andena, L.; Caimmi, F.; Leonardi, L.; Ghisi, A.; Mariani, S.; Braghin, F. (Procedia Engineering, 2016)
Bike and ski helmets are mainly made up of two layers: the external shell and the foam liner. The foam liner, typically made of expanded polystyrene (EPS) or polypropylene (EPP), is asked to provide energy absorption in case of impacts. Standard helmet design requires the foam to maximize this energy absorption, thus achieving large deformations (up to 25% in compression) while maintaining the stress level below a threshold value. To optimize the helmet construction in terms of foam composition, structure and density, reliable numerical models are required, which in turn need to be fed with accurate experimental data.